Does military spending stifle economic growth? The empirical evidence from non-OECD countries - Azam, Muhammad (Heliyon, 2020)
Undeniably, peace and long-term sustainable economic development are the prime agenda of all countries. This study aims to empirically evaluate the impact of military spending on economic growth for a panel of 35 non-OECD countries over 1988–2019. A multivariate regression model based on the augmented production function is used to achieve the objective of the study. The panel autoregressive distributed lag (ARDL)/pooled mean group (PMG) technique is employed, while, in addition the robust least squares and fixed-effect estimators are implemented for the robustness of the results. This study found a clear negative effect of military spending on economic growth. The pairwise Dumitrescu Hurlin panel causality test results exhibit bi-directional causality between military expenses and economic growth. Overall, these estimates provide strong support that military expenditure is not beneficial rather detrimental to economic growth. The empirical findings of this study suggest that policymakers need to redesign the military budget to stimulate economic growth and improve social welfare.